Upper surface imprinted membrane prepared by magnetic guidance phase inversion method for highly efficient and selective separation of Artemisinin - Bai, Mengqi; Qiang, Li; Meng, Minjia; Li, Binrong; Wang, Suao; Wu, Yilin; Chen, Li; Dai, Jiangdong; Liu, Yan; Pan, Jianming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
•Magnetic molecularly imprinted membrane is used to selectively separate Art and Are.•Aru was selected as the dummy template of Art for enhancing the Art selectivity.•Imprinted NPs are fixed on the up-surface for raising up the separation efficiency.•The separation efficiency can be tuned by the thickness of imprinted polymer. Molecularly imprinted membrane fabricated by conventional phase inversion method often suffers from low selectivity and low efficiency due to nonselective recognition sites resulted from usual swelling of the polymeric material and polymer-embedded imprinted sites. In this study, a new magnetic molecularly imprinted membrane (MMIM) with imprinted sites located and dispersed on the membrane up-surface was successfully prepared via phase inversion method by virtue of the magnetic field force for selective separation of Artemisinin (ART) and Artemether (ARE), in which magnetic imprinted particles coated by imprinted nanolayers with controllable thickness of ca. 10 nm were first synthesized and functioned as the original imprinted sites for the membrane. In comparison with the control membrane (MMIM0) without magnetic guidance, the magnetic molecularly imprinted membrane (MMIM1) exhibited significant enhancement in recognized adsorption and highly efficient separation for ART and ARE mixture owing to the imprinted sites concentrated on the up-surface. For the batch competitive permeation experiments, the value of βART/ARE for MMIM reached up to 5.98, higher than that of MMIM0 (βART/ARE=3.12). For the dynamic cross-flow separation system, the αvalue of MMIM1 in the initial time could be promoted to be 22.0, while that of MMIM0 was onlyα = 2.5. 1H NMR spectra and density functional theory (DFT) verified that the enhanced selective separation efficiency for MMIM1 towards ART and ARE could be originated from both the shape of imprinted cavities and the interaction between ART and functional groups. This work highlights that the dynamic separation system over magnetic molecularly imprinted membrane provides an alternative potential “applicable platform” for large-scale separation and extraction of natural products.